Hypothalamic‐pituitary‐adrenal axis and depression symptom effects of an arginine vasopressin type 1B receptor antagonist in a one‐week randomized Phase 1b trial. Issue 3 (9th February 2017) - Katz, David A.; Locke, Charles; Greco, Nicholas; Liu, Wei; Tracy, Katherine A.
Abstract: Background: Arginine vasopressin 1B receptor (V1B ) antagonists may have utility for the treatment of major depressive disorder (MDD). Methods: The V1B antagonist ABT‐436 ( N = 31) or matching placebo ( N = 20) was administered to MDD subjects for 7 days. The main study objectives were to assess the safety and hypothalamic–pituitary–adrenal axis (HPA) effects of ABT‐436 in MDD subjects. MDD symptoms were assessed using the 17‐item Hamilton Depression Rating Scale (HAM‐D‐17) and the subject‐rated Mood and Anxiety Symptom Questionnaire (MASQ). Results: The most prevalent safety finding associated with ABT‐436 800 mg QD was increased mild‐moderate diarrhea (68% v 5%, p < 0.001). Increased nausea (26% v 5%, p < 0.10), decreased systolic blood pressure (3.15–3.44 mmHg, p < 0.10) and increased heart rate (3.42–4.01 bpm, p < 0.05) were also associated with ABT‐436 800 mg QD. Basal HPA activity measured by 24‐hr urine total glucocorticoids was 25% lower with ABT‐436 than placebo ( p < 0.001). The reduction was, on average, larger in subjects with higher baseline urine total glucocorticoids. Results on plasma adrenocorticotrophic hormone (ACTH), urine, serum and saliva cortisol, and saliva cortisone also showed basal HPA attenuation with ABT‐436. Dynamic HPA activity measured by plasma ACTH and serum cortisol responses to corticotrophin releasing hormone (CRH) were 30–46% lower in ABT‐436 subjects (all p < 0.001). Each ABT‐436 subject showed response to CRH in or near the baseline range of responses. ABT‐436 was associated with more favorable symptom changes on two of five MASQ subscales (estimated effect size 1.47–1.86, p < 0.01) but not on HAM‐D‐17. Conclusions: The results support further clinical study of the antidepressant potential of ABT‐436. Abstract : ABT‐436, a potent and selective arginine vasopressin 1B receptor antagonist, or matching placebo was administered to major depressive disorder subjects for 7 days. ABT‐436 reduced both basal and dynamic activity of the hypothalamic‐pituitary‐adrenal access, and was associated with more favorable depressive symptom changes. The results support further clinical study of the antidepressant potential of ABT‐436.